Indicative Characteristics and Models of Innovative Thinking in The Thinking of Youth Today - Abdurakhmonov Khasan Ibroximovich (Scientific Trends, 2025)
This article analyzes the formation of innovative thinking in the thinking of today's young generation, its main forms of manifestation and development models. Attention is paid to the reflection of innovative thinking in education, technology, social activity and creative processes. The article scientifically highlights the role of young people in solving modern problems, their creative approaches and activities in promoting innovative initiatives.
Keywords: Innovative thinking, creativity, youth, model, modern thinking, technological development, creative approach.